Some factors affecting Stellantchasmus falcatus metacercaria in laboratory. - Wongsawad C. (2014)
Killing factors, various temperatures and solutions were studied in the laboratory on Stellantchasmus falcatus metacercaria in half-beaked fish (Dermogenus pusillus). Killing criteria followed the Movability Index from 1.000 within 24 hours. The metacercariae were collected from Chiang Mai moat. They were incubated in 0.85 % NaCl at -20 degrees C, room temperature, 4 degrees, 37 degrees, and 65 degrees C. The in vitro investigation showed that at -20 degrees C and 65 degrees C, the worms were killed within 18 and 2 hours, respectively, while other temperatures produced no effect. The solutions investigated were NaCl (10, 20, 30, and 40%), lemon juice (25, 50, 75, and 100%), acetic acid (5, 10, 20, and 30%), vinegar (1, 3, and 5%) and water as a control. The worms were killed in NaCl at 20, 30, and 40% within 12, 6, and 2 hours, respectively. Acetic acid at 5% and 10% killed the metacercaria within 12 and 6 hours while at 20% and 30%, within 2 hours. The killing effect of 3% vinegar was found within 18 hours and of 5% vinegar within 12 hours. Lemon juice showed no killing effect.